2016
DOI: 10.1021/acs.energyfuels.6b01597
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Oxygen-Containing Compounds and Its Significance on Total Organic Acid Content in Crude Oils by ESI Negative Ion FT-ICR MS

Abstract: In the present work the distribution of oxygen compounds in the total organic acid content of ten crude oils was assessed by means of negative ion electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry ((−) ESI FT-ICR-MS). As a first attempt, the relative abundance of the O2 class was related to the total acid number (TAN) for samples following the state of the art, and no positive correlation was achieved. Therefore, we performed the selective isolation of acidic compounds via sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…O'Reilly () discussed the need to consider the presence of both degradation intermediates and material synthesized from bacterial growth. The terms “oxygen‐containing compounds” (Rojas‐Ruiz and Orrego‐Ruiz ) and “oxygen‐containing organic compounds” (OCOCs; Eigenmann et al ) have been used in the scientific literature to describe the types of chemicals that are the focus of this research. In this manuscript, we use the term “OCOCs,” as it describes their chemistry without making assumptions about their biological source.…”
Section: Introductionmentioning
confidence: 99%
“…O'Reilly () discussed the need to consider the presence of both degradation intermediates and material synthesized from bacterial growth. The terms “oxygen‐containing compounds” (Rojas‐Ruiz and Orrego‐Ruiz ) and “oxygen‐containing organic compounds” (OCOCs; Eigenmann et al ) have been used in the scientific literature to describe the types of chemicals that are the focus of this research. In this manuscript, we use the term “OCOCs,” as it describes their chemistry without making assumptions about their biological source.…”
Section: Introductionmentioning
confidence: 99%
“…The O 2 species with a DBE of 6 were likely a phenol core fused with a furan core. Furthermore, Orrego-Ruiz and Rojas-Ruiz 50 concluded that the O 2 compounds found in the acidic fraction are confined to DBE <10, while the nonacids to DBE >10. The relative abundance of O 3 class compounds with DBE values of 2, 9, 11, and 14 was higher than that of compounds with adjacent DBE values, as shown in Figure 13 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The compounds with DBE of 1 were the most abundant O2 species, accounting for 10%, which were likely to be fatty acids. 32 The O2 species with DBEs ≥2 were assigned to naphthenic/aromatic structures containing a carboxyl moiety. 33 For instance, the O2 species with a DBE range of 2–6 could be naphthenic acids containing one to five naphthenic rings.…”
Section: Resultsmentioning
confidence: 99%